Effect of scraping on hypertensive ischemic stroke based on "Qi Circulation" theory (基于“一气周流”理论刮痧干预高血压缺血性脑卒中的疗效观察) - LIU Bin (刘彬); YU Yanlan (余艳兰); GAO Ziqi (高子琪); FENG Shuihua (奉水华); YANG Nan (杨楠); GUO Yuan (郭元); (廖若夷) (中西医结合护理)
Objective To observe the clinical effects of scraping on hypertensive ischemic stroke based on the theory of " Qi Circulation " . Methods Totally Sixty patients with hypertensive ischemic stroke who met the inclusion criteria were randomly divided into observation group and control group, with 30 patients in each group. All patients received conventional drugs and rehabilitation nursing, and patients in the observation group were treated with a 30-45 minutes of meridian scraping treatment based on "Qi Circulation " theory, once a week for 4 weeks. The changes of blood pressure, homocysteine (Hcy), matrix metalloproteinase-9(MMP-9) and blood lipid indexes including total cholesterol (TC), triglyceride (TG), high-density lipoproteincholesterol(HDL-C) and low-density lipoproteincholesterol(LDL-C) before and after intervention were compared between the two groups. Results Level of blood pressure, Hcy, TC, TG and LDL-C in 2 groups were decreased after intervention (P＜0. 05), better improvement was reported in the observation group than that in the control group (P＜0. 05). Conclusion Scraping based on the theory of "Qi Circulation" can effectively reduce blood pressure, Hcy, MMP-9, TC, TG, LDL-C levels in patients with prehypertensive ischemic stroke, and can be promoted and applied as a safe and effective adjuvant therapy. (目的 观察基于“一气周流”理论刮痧干预高血压缺血性脑卒中的临床疗效。方法 将符合纳入标准的60例高血压缺血性脑卒中患者随机分为观察组和对照组, 各30例。对照组给予常规药物及康复护理对症支持治疗; 观察组在对照组基础上基于“一气周流”理论, 选择相应经络刮痧, 每次45～60min, 每周1次, 两组疗程均4周。比较两组患者干预前后血压、同型半胱氨酸(Hcy)、基质金属蛋白酶-9(MMP-9)和血脂［总胆固醇(TC)、甘油三酯(TG)、高密度脂蛋白胆固醇(HDL-C)、低密度脂蛋白胆固醇(LDL-C)］变化情况。结果 两组患者血压、Hcy、TC、TG、LDL-C均较干预前降低, 差异有统计学意义(P<0. 05), 且观察组的下降幅度大于对照组(P<0. 05)。结论 基于“一气周流”理论刮痧可有效降低预高血压缺血性脑卒中患者血压、Hcy、MMP-9、TC、TG、LDL-C水平, 可作为临床安全、有效的辅助手段推广应用。)